Single port laparoscopic cholecystectomy in Situs Inversus Totalis - Guillermo Aldana; Hedda Uribe; William Rios (Case Reports)
Symptomatic cholelithiasis is a highly prevalent disease in Colombia, though its presentation in patients with situs inversus totalis has rarely been described. This report describes the case of a patient with symptomatic cholelithiasis and situs inversus totalis who underwent a single-port laparoscopic surgery after concomitant gallstones were ruled out. This procedure is a minimally invasive technique of SILS (Single Incision Laparoscopic Surgery). Situs Inversus is a rare genetic disorder which is characterized by the transposition of the abdominal and chest organs through the sagittal plane, having a so-called “mirror image” effect. While the etiology is still unclear, it is often attributed to a genetic predisposition caused by an autosomal recessive gene of incomplete penetrance. The presence of symptomatic vesicular lithiasis in a patient with SIT not only creates diagnostic doubt but also presents a real challenge for treatment as any surgical procedure (especially laparoscopic cholecystectomy) will be more difficult due to the anatomical abnormalities of the patient.